(untitled) (Mustansiria Dental Journal, 2024)
Background: The material most frequently employed in the dental industry is polymethyl methacrylate (PMMA). Temporary dental restorations, including those for complex indications such as implants or large-span bridges, are manufactured using this material. However, its numerous limitations render it unsuitable for application in all situations. Consequently, individuals utilizing removable prostheses must be concerned regarding the potential for fracture. The purpose of this study: examined the effects of various particle sizes of 5% hydroxyapatite (which was prepared from ostrich eggshell powder) on the roughness and compressive strength of heat-cured acrylic resin. Materials and Methods: A total of 28 cylindrical samples composed of pink heat-treated acrylic resin were fabricated and subsequently categorized into four experimental groups; Group A (Control without any additive), Group B (Particle size 80µm), Group C (Particle size 70 µm), and Group D (Particles Size 50 µm). Each group consisted of seven samples categorized according to the varying sizes of hydroxyapatite particles. The test groups homogenously blended at a weight percentage of 5% of ostrich eggshell powder. Subsequently, an assessment was conducted to determine the collective compressive strength and surface roughness of this groups. Result: The results of the investigation showed significant variations in compressive strength for group B (107±3.742 MPA), group C (103.43±5.192 MPA), and group D (98.43±7.323 MPA) concerning the different sizes of hydroxyapatite particles compared to group A (74±4.163 MPA). While there was a significant increase in surface roughness for groups B (3.22±0.014), C (2.41±0.018), and D (2.36±0.077) compared to group A (1.451±0.073). Conclusion: Varying the particle size of hydroxyapatite added to the thermosetting acrylic resin (80μm, 70μm, and 50μm) increases both the material’s compressive strength and surface roughness.